Morphological and functional aspects of anthers from species of Solanum,Sect. Cyphomandropsis - Passarelli, Lilian (2006)
The study of anther development of Solanum sect. Cyphomandropsis species (Solanum confusum Morton, Solanum glaucophyllum Desf. and Solanum stuckertii Bitter) provide information about differences between the anther wall layers and placentoid behaviour at maturity and according with the floral syndrome. It is known that in Solanum species with vibratory mode of pollen release, anther wall is thick with four or more layers and the placentoid staid expanded during anthesis. In Solanum species with a bellow like mechanism of release (e.g. section Pachyphylla) pollen wall is thin (one or two layered) and the palcentoid presents a double expansion at maturity being collapsed at anthesis time. The anther locule stays empty allowing the pollen to be bellowed out. This feature was known exclusively for sect. Pachyphylla but in this work it is observed that it is extended in the genus. In section Cyphomandropsis with both pollen release modes working together intermediate anther morphology is found and anther behavior at anthesis time is similar to that of section Pachyphylla.